Metal Halide Perovskites for Applications in Biomimetic Devices - Wending Chu; Lei Su (Inorganics)
Metal halide perovskites have demonstrated exceptional multifunctionality, finding applications in photovoltaics, light-emitting devices and sensors, which has stimulated intense research interest. Recently, their integration into biomimetic devices has emerged as a promising frontier, exploiting the unique optoelectronic properties of perovskites to mimic biological functions. This review provides a comprehensive analysis of recent advances in the use of metal halide perovskites for biomimetic applications, focusing on their role in different device configurations and fabrication techniques. We elucidate the mechanisms that drive their performance and demonstrate their potential as versatile materials for high performance biomimetic devices. By exploring the intricate interplay between material properties and device functionality, we highlight the transformative potential of metal halide perovskites in creating more efficient, adaptable and biologically inspired technologies. Finally, we discuss future research directions to maximise their application scope, with the aim of bridging materials science and bioengineering for innovative device development.